PENGARUH JOKOWI EFFECT TERHADAP REAKSI SAHAM PERUSAHAAN YANG TERDAFTAR PADA JAKARTA ISLAMIC INDEX - Abdullah, Lalu Muhamad; Fitriani, Dyah (Universitas Ahmad Dahlan, 2013)
This study examined, abnormalreturn differences, and differences in the volume traded on the stock companies listed on the Jakarta index Islamic Index before and after the announcement of the nomination of events Joko Widodo as President. Population in this research that companies listed on the index JII. Objects in this study is 30 companies. The sampling technique means that all members of the saturated sample or population used as a sample in the study. Data collection techniques with methods of documentation obtained from yahoo finance, IDX. Analysis tools used in this research that Paired samples t-test and One Sample T-test with SPSS 20 software. The test results on the effect of Jokowi effect on the reaction of the company’s shares are listed on the index can be concluded there is abnormalreturn JII daily before and after the announcement. However, there were no differences in abnormalreturn and volume of sales before and after the announcement.